2022
DOI: 10.1007/s00404-022-06494-4
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative mapping and structured reporting of pelvic endometriotic lesions on dynamic ultrasound and its correlation on laparoscopy using the #ENZIAN classification

Abstract: Purpose: The objective of this study was to evaluate and compare the diagnostic performance of ultrasonography (USG) assessment using structured reporting with intraoperative laparoscopic assessment in deep in ltrating endometriosis (DIE) using the recent update of the #ENZIAN classi cation.Methods: This was a retrospective study conducted in Tertiary Multi-disciplinary Endometriosis Care Hospital over a period of 8 months which included 50 patients who underwent a planned laparoscopic endometriosis excisional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
3
15
0
1
Order By: Relevance
“…Six articles ultimately remained to be analyzed in our meta-analysis. [15][16][17][18][19][20] Characteristics of Included Studies Table 1 summarizes the main characteristics of the primary studies included in our meta-analysis. Data about 834 patients was available.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six articles ultimately remained to be analyzed in our meta-analysis. [15][16][17][18][19][20] Characteristics of Included Studies Table 1 summarizes the main characteristics of the primary studies included in our meta-analysis. Data about 834 patients was available.…”
Section: Search Resultsmentioning
confidence: 99%
“…Five studies included a non-consecutive series of patients. [15][16][17][18]20 In one study, this information was not reported. 19 The diagnostic test used to conduct these studies was a TVU, and all studies used laparoscopic surgical findings with histopathological confirmation as the reference test, our reference standard.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine sehr gute Übereinstimmung der sonografischen Klassifikation mit der #Enzian-Klassifikation (neue Klassifikation) mit der chirurgischen Klassifikation haben Di Giovanni et al in einer retrospektiven Studie nachgewiesen [18]. Dies bestätigten Montanari in einer prospektiven Multicenterstudie mit 745 Patienten aus 7 internationalen Zentren [19] und Bindra et al [20]. Frage 4…”
Section: Die #Enzian-klassifikationunclassified
“…The ENZIAN classification was originally developed in 2003 but the latest update in 2021, called #ENZIAN, offers a comprehensive pictorial mapping of endometriosis and is suitable for both diagnostic imaging and laparoscopy [22]. The ENZIAN classification system locates the endometriosis into compartments: compartment A (vagina and rectovaginal septum), compartment B (uterosacral ligaments to pelvic floor), and compartment C (rectum and sigmoid colon) and has additional description for O (ovarian), T (tubo-ovarian complex), P (peritoneal), FA (adenomyosis), FB (urinary bladder), FU (ureter) and FI (intestinal) [22][23][24]. Figure 1 illustrates the #ENZIAN classification with overview of potentially affected organs and compartments.…”
Section: Standardising Ultrasounds For the Diagnosis And Classificati...mentioning
confidence: 99%